A systems approach to strategy in third sector organizations - Simaens, A.; Roome, N. (42nd Annual Association for Research on Nonprofit Organizations and Voluntary Action (ARNOVA) Conference, 2013)
Third sector organizations (TSOs) operate in arenas of policy, practice and need where there is a high degree of complexity. Complexity arises because the problems TSOs address are often connected at the level of the client or community, and because the interests, goals and actions of different TSOs interact. These characteristics define what have been termed ‘meta-problems’, ‘messes’ or ‘wicked problems’. These problems require ‘systems’ responses. Systems responses involve strategies that fulfill organizational mission, while also contributing to integrated solutions for people and their problems. With this starting point, the paper develops a conceptual framework that provides insight into the strategic management of TSOs using a systems approach to understand organizational and social reality as parts of a complex whole. From this analysis we derive five propositions that address the implications of complexity of this kind for strategy making by TSOs.